Effect of Phototherapy on Serum Calcium Level in Neonatal Jaundice - Hina Sohail, Alia Halim, Sahira Aaraj, Nazia Mushtaq (Journal of Islamic International Medical College)
Objective: The aim of this study was to determine the effect of phototherapy induced hypocalcemia in icteric newborns and to compare it between preterm and term neonates. Study Design: Quasi experimental study. Place and Duration of Study: Pakistan Air Force (PAF) hospital Islamabad, from 1st July 2021 to 31st January 2022. Materials and Methods: A total of 62, full term and late preterm neonates, requiring phototherapy for indirect hyper-bilirubinemia were included. The serum calcium levels were checked, pre and post phototherapy or 48 hours after start of phototherapy whichever came earlier. The data of patients, regarding gender, gestational age, chronological age and mode of delivery was recorded. The data was analysed in SPSS version 22. The frequency and percentages were calculated for qualitative variables i.e gender and mode of delivery. The mean and standard deviation were calculated for quantitative variables i.e age, gestational age, duration of phototherapy, pre and post phototherapy serum calcium levels. The paired sample t test was applied to compare pre and post phototherapy serum calcium levels. The p-value < 0.05 was considered statistically significant. Results: There were 39 (62.90%) males and 23 (37. 10%) females, with mean age of 4.52 ± 1.25 days. The mode of delivery was cesarean section in 41 (66.13%) cases while 21 (33.87%) were delivered as vaginal delivery. The mean gestational age was 38.11 ± 1.49 weeks. The mean duration of phototherapy was 3.17 ± 0.55 hrs. The mean value of pre and post therapy serum calcium level was 9.59 ± 0.52 mg/dl and 9.07 ± 0.44 mg/dl respectively (p value = 0.0001). The post phototherapy calcium levels did not have any significant association with gestational age, gender and chronological age of the newborns i.e. the p value was 0.174, 0.269, 0.134 respectively. Conclusions: Phototherapy resulted in a significant reduction in serum calcium levels after 48 hours; however, none of the neonates developed hypocalcemia